Allogeneic stem cell transplantation for chronic myelomonocytic leukemia: a report from the Societe Francaise de Greffe de Moelle et de Therapie Cellulaire. (7th March 2013) - Park, Sophie; Labopin, Myriam; Yakoub‐Agha, Ibrahim; Delaunay, Jacques; Dhedin, Nathalie; Deconinck, Eric; Michallet, Mauricette; Robin, Marie; De Revel, Thierry; Bernard, Marc; Vey, Norbert; Lioure, Bruno; et al.
Abstract: Objectives and methods: Chronic myelomonocytic leukemia (CMML) is a severe disease for which allogeneic stem cell transplantation (allo‐SCT) remains the only potentially curative treatment. We describe a retrospective study determining prognostic factors for outcome after allo‐SCT in consecutive 73 patients with CMML reported to the SFGM‐TC registry between 1992 and 2009. Results: At diagnosis, median age was 53 yrs, and 36% patients had palpable splenomegaly (SPM). 48, 13, and 9 patients had good, intermediate, and poor risk karyotype, respectively, according to IPSS, 61% patients had CMML‐1, and 39% had CMML‐2. 41/31/1 cases had an HLA‐identical sibling, an unrelated and haploidentical donor, respectively. 43 patients received reduced‐intensity conditioning. With a median follow‐up of 23 month, acute grade 2–4 and chronic GVHD developed in 21 and 25 patients, respectively. The 3‐year OS, NRM (non‐relapse mortality), EFS, and CIR (cumulative incidence of relapse) were 32%, 36%, 29% and 35%, respectively. OS was not influenced by the CR status, marrow blasts% at allo‐SCT, prior treatments, and cGVHD. Using multivariate analysis, year of transplant < 2004 (YOT) ( P  = 0.005) was associated with higher NRM, YOT < 2004 ( P  = 0.04) and SPM at allo‐SCT ( P  = 0.02) with lower EFS, and YOT < 2004 ( P  = 0.03) and SPM at allo‐SCT ( P  = 0.04) with poorer OS. Conclusions: Allogeneic stem cell transplantation is a valid treatment option for patients with CMML, and its outcome has improved with YOT > 2004. Splenomegaly seems to be a negative factor of OS and EFS in this series.